Molecular Characterization of the Product Compounds Formed Upon Heterogeneous Chemistry of Ozone With Riverine Surface Microlayer. Issue 18 (18th September 2022) - Wang, Yiqun; Deng, Huifan; Li, Pan; Xu, Jinli; Jiang, Bin; Pang, Hongwei; Gligorovski, Sasho
Abstract: Ozone (O3 ) is an important trace gas and oxidant in the atmosphere which sources and sinks are not well understood. In this study we measured the uptake coefficients of O3 (100 ppb) on authentic riverine surface microlayers (SML) collected on three different places on Pearl River in Guangzhou by a vertical wetted wall flow tube reactor which enables to estimate the deposition velocity of O3 on the fresh water surface. The product compounds formed upon interfacial reactions of O3 with the SML have been investigated by a Fourier transform ion cyclotron resonance mass spectrometry. About 10 times more product compounds were formed upon ozonolysis on the SML sample collected in a transportation hub close to the Estuary zone compared to the products formed upon ozonolysis on the SML sampled at the upper reach of the river at the periphery of Guangzhou. Moreover, 933 nitrogen (N)‐containing organic compounds which are associated with nitrooxy amines, organonitrates, nitroaromatics, and peroxyacetyl nitrates were formed upon heterogeneous reaction of ozone with the SML collected near the Estuary zone compared to 165 N‐containing compounds formed upon ozonolysis of the SML sample collected at the periphery of the city. Hence, the formed condensed phase product compounds through the reactions of ozone with the riverine SML can affect the freshwater biodiversity. An important fraction of brown carbon compounds was formed, which may be released to the air by wind‐wave interactions and influence the chemical composition of the atmosphere and thus, radiative forcing of the aerosols. Plain Language Summary: Ozone (O3 ) in the atmosphere is a greenhouse gas and also an air pollutant. Deposition of ozone to the sea is an important removal path of ozone. In this study, we assess how the deposition of ozone to the freshwater surface can affect the environment. For this purpose, we measured the uptakes of ozone on a real riverine surface microlayers sampled on three different places on Pearl River in Guangzhou, China. These values served to estimate the ozone deposition on Pearl River. The ozone induced chemical transformation of the organic material enriched at the riverine surface, was analyzed by high‐resolution mass spectrometry. The results indicate that the number of the compounds increase and the nature of the organics is altered upon ozone reactions with the riverine surface microlayer. The newly formed compounds can affect the biodiversity of the freshwater and pose environmental concern. One fraction of the formed compounds which are volatile by nature can escape the water surface and reach the atmosphere, thereby affecting the air quality in the urban environment. Key Points: The ozone deposition to the Riverine surface microlayer (SML) is enhanced due to its chemical reactivity with the organic compounds High load of light‐absorbing and toxic compounds, due to ozonolysis, is enriched at the SML as the river is approaching to the sea Fourteen times more CHO product compounds are formed upon ozonolysis of SML in Estuarine zone than at the periphery of the city